Using siRNA-Based Anti-Inflammatory Lipid Nanoparticles for Gene Regulation in Psoriasis - Zeng A; Liu Y; Wang P; Cao Y; Guo W (International Journal of Nanomedicine)
Aizhong Zeng,* Yuanyuan Liu,* Ping Wang, Yufei Cao, Wei Guo School of Life Science and Technology, China Pharmaceutical University, Nanjing, 211112, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Guo, School of Life Science and Technology, China Pharmaceutical University, Nanjing, 211112, People’s Republic of China, Email guowei1205@cpu.edu.cnBackground: Psoriasis is a chronic inflammatory autoimmune disease, yet it affects hundreds of millions of people. Long-term effective intervention of the disease by targeting the causative genes via RNAi (RNA interference) has become a reality. However, its further application is hindered by inflammatory side effects caused by delivery systems such as LNP (lipid nanoparticles).Purpose: This study aimed to develop a novel anti-inflammatory LNP rationally tailored for topical application in psoriasis and to validate its potential to deliver Stat3 (signal transducer and activator of transcription 3) siRNA for the treatment of psoriasis.Methods: To assess the transfection efficiency, anti-inflammatory capacity of LNPs. The therapeutic effect of modified anti-inflammatory LNP delivery of Stat3 siRNA on psoriasis was evaluated both in vitro and in an imiquimod-induced mice.Results: LNPs exhibit both superior transfection efficiency and significant anti-inflammatory effects. In vitro functional studies showed that in an inflammatory DC model, anti-inflammatory LNP (C8B2) inhibited inflammatory mediators much better than classical LNPs by delivering Stat3 siRNA; in pathological HaCat cells, Stat3 siRNA reduced cell proliferation and promoted apoptosis. In the imiquimod-induced mouse model, the C8B2-si-Stat3 group demonstrated a clear reduction in psoriasis progression, whereas the C8B2 carrier group also exhibited a notable decrease in inflammation.Conclusion: In this study, we successfully developed a novel anti-inflammatory LNP, which demonstrated notable advantages in delivery capacity, anti-inflammatory effect, and targeting therapy against STAT3, providing new ideas and strategies for nucleic acid therapy of psoriasis. This LNP platform could be broadly applicable to various inflammatory conditions, offering a versatile tool for targeted gene modulation and inflammation control. Keywords: psoriasis, lipid nanoparticle, RNA interference, STAT3